Front Cover: Dyn[n]arenes: Versatile Platforms To Study the Interplay between Covalent and Noncovalent Bonds (Eur. J. Org. Chem. 2/2022). Issue 2 (14th January 2022) - Vial, Laurent; Perret, Florent; Leclaire, Julien
Abstract : The Front Cover illustrates the stereoselective covalent self‐assembly in water of 1, 4‐bisthiophenol building blocks into dyn[n]arenes. The background photo was taken in Lyon, where most of the chemistry presented in this review was performed. More information can be found in the Review by L. Vial, F. Perret, and J. Leclaire .